Al-Majusi treatment of physical diseases using drug therapy and surgical manipulation - Mohamed, Nazhirah; Shuriye, Abdi Omar (IIUM Press, 2011)
In this chapter, we wish to investigate on al-Majusi's treatment of physical diseases under two major headings of drug therapy and treatment by surgical manipulation. 'Ali b. al-'Abbas al-Majusi (c.925-994) was a Persian physician and is best known for his medical encyclopedia entitled Kitab Kamil as-Sina'a at-Tibbiyya ("Complete Book of the Medical Art"). The main focus ofthe chapter is to underscore his methid oftreatment. The chapter also reviews Kitab al-kamil; the most systematic, practical and concise medical encyclopedia. This work consists of twenty treatises on the theory and practice of medicine. Our aim in this chapter is to increase awareness on the subject matter.